(untitled) (Journal of the Management Sciences, 2026)
This paper examines healthcare administration and the efficacy of hypertension treatment in Nigeria. It argues that the Nigerian system needs to adopt new mechanism of using evidence-based medicine to treat hypertension. The paper uses data derived from questionnaire surveys and interviews of officials of public and private sectors, hospitals, and other healthcare stakeholders. The secondary data consisted of the review of related government reports, government websites, academic and professional journals. Data were analyzed to determine the methods of treating hypertension disease and challenges facing the healthcare system administration in Nigeria. The conceptual framework is based on evidence-based medicine and evidence-based treatment. The findings suggest that the negative used of evidence-based medicine practice has reduced physicians’ efficiency in the treatment of hypertension in Nigeria. There is also evidence that the lack available modern medical equipment has negatively impacted the practice of new methods of treating hypertension with e-medicine. Some challenges preventing the adoption of evidence-based hypertension treatment were identified and recommendations for appropriate policies that could address the current impediments were offered.